False Alarms vs. Misses: Subjective Trust as a Mediator between Reliability and Alarm Reaction Measures. (September 2015) - Chancey, Eric T.; Bliss, James P.; Liechty, Molly; Proaps, Alexandra B.
Research suggests that signaling system false alarms tend to affect operator compliance, whereas misses tend to affect operator reliance. Conceptually, false alarms and misses affect compliance and reliance via independent cognitive processes, assumed to be two types of trust. The purpose of this study was to test for these underlying processes using a subjective estimate of trust. Method: Using a sample of 44 college students, we tested for trust as a mediator between reliability (90%, 60%) and reliance, compliance, and response rate, for a false alarm prone (FP) system and a miss prone (MP) system. Results: As predicted, trust mediated the relationships between reliability and signal compliance and response rate, but only for the FP system. Additionally, the MP system more directly affected reliance, whereas the FP system more directly affected compliance. Applications of this work indicate that designing for trustable signaling systems may be more important for FP systems.